Vico, filósofo del alba: la teoría antropológica de los orígenes (pp. 283-292). Trad. de Jose M. Sevilla. - Battistini, Andrea (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 9-10 (1998). 498 págs. ISBN 1130-7498